Model of The Students Thinking in Completing Vector Analysis through Physics Context - Fahruddin; Werdhiana, I Komang; Darsikin, Darsikin (Universitas Tadulako, 2017)
This research was purposed to describe the way of the students' thinking in completing the vector-based test by physical context. The instrument of this research consisted of the respondent selection test (TSR), logical test with thinking-aloud (TA), and interview guidance. Respondents of this research were six students in one of the senior high school in Palu. Collecting data was held by applying a thinking-aloud (TA) and interview which recorded by using a video camera. The interview was conducted to find out supporting data in analyzing the result of thinking-aloud (TA) data. The analyzing data of the way of students' thinking can be seen from every step of their respondents in completing the test by using physical context. Generally, there are two thinking models that are deductive thinking and inductive thinking. In the analysis of the results of TA and interviews, obtained that respondents are more dominant used of deductive thinking in completing the test than inductive thinking. It was influenced by the teacher's method in providing the test when the teaching-learning process and the students' usage in completing the test.